Successful treatment outcome of primary melioidosis pneumonia-a case report from Bangladesh. (December 2016) - Afroze, Samira; Rahman, Md.; Barai, Lovely; Hossain, Md.; Uddin, Khwaja
Abstract Background Melioidosis is endemic in tropical Australia and Southeast Asian countries and its causative organismBurkholderia pseudomallei is a recognized cause of pneumonia in these regions. Recent isolation of the organism in the soil of Kapasia, Gazipur, Bangladesh has proven its exposure among the population residing in endemic areas of our country. Pneumonia is the most common presentation of melioidosis. Acute, subacute and chronic pneumonia due toB. pseudomallei can present as primary or secondary pneumonia. Treatment of such cases are challenging as well. Till date, few cases of acute and chronic pneumonia due to melioidosis occurring in local Bangladeshis as well as in returning travelers to Europe have been reported. To the best of our knowledge, this is the first reported case of primary melioidosis pneumonia declared cured after a 27 weeks of treatment regimen from Bangladesh. Case presentation A 43-year-old Bangladeshi gentleman, known diabetic, hypertensive, smoker, presented with the complaints of recurrent episodes of low to high grade intermittent fever, productive cough with occasional haemoptysis and 10 kg weight loss over one and half months. Poorly responding to conventional antibiotics, he was suspected as a case of pulmonary tuberculosis. Examination and investigations revealed left sided consolidation with cavitary lesion, hepato-splenomegaly and sputum analysis confirmed growth ofBurkholderia pseudomallei . The patient was successfully treated as a case of primary melioidosis pneumonia. Conclusion Often misdiagnosed and empirically treated as tuberculosis, untreated melioidosis pneumonia may even lead to death. Therefore, melioidosis should be suspected in appropriate clinical scenario in patients with a history of residing in or traveling to endemic areas. In Bangladesh, time has come to explore whether melioidosis should be considered as an emerging infectious disease.